VITAMIN-A (BREAST MILK) ASSESSMENT BETWEEN RURAL AND URBAN AREA OF BALOCHISTAN BY H.P.L.C. - Muhammad Aziz; Saima Jadoon; Shafia parveen (Journal of University Medical & Dental College, 2013)
ABSTRACT The vitamin A (retinol) content in human milk was determined among 30 mothers.15 belonged to urban area and 15 belonged to rural area of Balochistan. Milk samples were obtained from Quetta urban and Mastung rural Districts to show the nutrition difference present between urban and rural population. Materials and methods: A rapid sensitive H.P.L.C method is used for separation and quantification of retinol in breast milk. The column used was Bonda pak C18 .The mobile phase CH3OH:H2O and the wavelength 325nm provided an excellent separation of this compound without interfering peak. Result: The vitamin A were found in the range 0.60-2.4ug/L in Quetta and 0.21-1.0ug/L in mastung Lactating women in rural part of Balochistan have lower milk vitamin A concentrations than lactating women in urban part of Balochistan. Conclusion: Results also show that the required concentration of vitamin A is not sufficient for the new born in mother milk and it also decreases with the passage of time in human milk.